Impact of high bleeding risk and associated risk factors on major adverse cardiovascular or cerebrovascular events in primary percutaneous coronary intervention treated ST-elevation myocardial infarction - Kesti, Henri; Mattila, Kalle; Jaakkola, Samuli; Lehto, Joonas; Söderblom, Nea; Kalliovalkama, Kalle; Porela, Pekka (Elsevier BV, 2026)
Background
After percutaneous coronary intervention (PCI), patients at high bleeding risk (HBR) according to The Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria have increased risk for ischemic complications. The underlying cause is not well documented. The aim of this study was to assess the ischemic risk among ST-elevation myocardial infarction (STEMI) patients classified as HBR according to the ARC-HBR and to identify individual risk factors.
Methods
Consecutive STEMI patients treated with primary PCI in a Finnish tertiary hospital between 2016 and 2022 were identified using a database search. Data was collected by reviewing electronic patient records. Bleeding risk was assessed according to the ARC-HBR criteria. The primary endpoint was 1-year major adverse cardiovascular or cerebrovascular event (MACCE).
Results
In total, 1367 STEMI patients were included. Cumulative incidence of MACCE was 19.5 % among HBR and 6.32 % among non-HBR. From the ARC-HBR criteria, multivariable competing risk analysis identified use of non-steroidal anti-inflammatory drugs or steroids and active malignancy as risk factors for MACCE. Diabetes and left ventricular ejection fraction <35 % were MACCE predictors and both were more prevalent among HBR patients. Dual antiplatelet therapy duration of ≥3 months significantly reduced risk of MACCE and was less prevalent among HBR.
Conclusions
The higher observed ischemic risk among HBR patients might not be explained by bleeding risk status itself but rather with some of its components and other underlying comorbidities and management strategies. These findings may be useful when evaluating the balance of ischemic and bleeding risks based on patient-specific risk factors.